Visual selection functional aptitude in the frame of Interbehavioral Psychology - Grajeda Montalvo, Alex Teofilo (2019)
A synthesized review of visual selection aptitude is presented, within the psychological metatheory called Interconductual Psychology. In principle, we emphasize the importance that learning, based on its biological and of stimulation bases, has for human development. Subsequently Interconductual Psychology is presented as a proposal of psychological system with substantial differences to other systems. Finally, the functional taxonomy developed by Ribes & Lopez (1985) is presented, as a different proposal of characterization of psychological development; and within it we highlight selectory function and its hypothetical relationship with learning to read.